Public Private Health Care Facility Utilization among Diabetic People in an Urban Area: A Descriptive Study - Yadav, Kamlesh Prasad; Mishra, Raman; Yadav, Birendra Kumar; Uprety, Samyog; Jha, Nilambar (MedS Alliance Journal of Medicine and Medical Sciences, 2021)
INTRODUCTION: Diabetes was considered the disease of affluent and imposes a significant burden on the health services. The modalities of diabetes therapies are different in different parts of the world. However, studies regarding public or private healthcare utilization are lacking in Nepal. Therefore, this study was designed to assess public private health care facility utilization among diabetic people in an urban area of Ithari, Nepal. MATERIALS AND METHODS: A community based cross-sectional study was conducted in Itahari, Submetropolitan of Sunsari district in the Koshi zone of Nepal from September 2017 - September 2018. The study population included 221 participants of age 25 years and above, diagnosed with type 2 Diabetes. Multi-stage proportionate random sampling method was adopted to select the participants. Chi square test was applied to find out the association and p<0.05 is considered significant. RESULTS: Out of the total (221) participants, 55.7% were aged 45-64 years with male of 50.2%. Higher proportion of participants above poverty line (79.7%) were used private healthcare facilities. Among the participants those reported less or equal to two hours waiting time, majority (90.8%) had gone to private healthcare facilities, whereas those reported more than two hours waiting time, majority (70.8%) had gone to public healthcare facilities for the treatment which was found statistically significant (p=0.0002). CONCLUSIONS: Maximum participants prefer private health care services as compared to government health services for their treatment. Therefore, additional community based studies are needed to include larger study populations in order to help healthcare providers develop proper health care programs for these patients.